Improving micro-hardness of stainless steel through powder-mixed electrical discharge machining - Mohd Zain, Zakaria; Ndaliman, Mohammed Baba; Khan, Ahsan Ali; Ali, Mohammad Yeakub (SAGE Publications Ltd, 2014)
Powder-mixed electrical discharge machining (PMEDM) is the technique of using dielectric fluid mixed with various types of powders to improve the machined surface output. The process is fast gaining prominence in electrical discharge machining (EDM) industry. The objective of this investigation is to determine the ability of tantalum carbide (TaC) powder-mixed dielectric fluid to enhance the surface properties of stainless steel material during EDM. The properties of investigated are the micro-hardness and corrosion characteristics of the EDMed surface. Machining was conducted with 25.0g/L concentration of TaC powder in kerosene dielectric fluid. The machining variables used were the peak current, pulse on time and pulse off time. The effects of variables on the micro-hardness of the EDMed surface were determined. Corrosion tests were also conducted on the samples that exhibited higher hardness. Results showed that the EDMed surface was alloyed with elements from the TaC powder. The micro-hardness obtained with PMEDM is about 1,200Hv. This is about 1.5 times obtained without TaC powder in the dielectric fluid. The loss in weight during corrosion test was found to be 0.056 ug/min for PMEDM which was lower than the lowest value of 10.56 ug/min obtained for the EDM without powder dielectric fluid.